Religious liberty in Western and Islamic law - Kalanges, Kristine (Oxford : Oxford University Press, 2012)
Weaves together international and comparative law, religion, international relations, comparative politics, and legal history to illuminate and address the theoretical and practical dimensions of a significant human rights problem.
Description based on online resource; title from PDF title page (viewed on Apr. 20, 2012).
Includes index.
Keywords: Freedom of religion